2018
DOI: 10.1177/1071100718755473
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Diagnosis and Other Factors on Patients’ Expectations of Foot and Ankle Surgery

Abstract: Level II, cross-sectional study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…More than patients with other foot and ankle pathologies, patients with HV typically expect the ability to comfortably wear shoes and increase their shoe wear variety. 1 Studies on this topic generally agree that patients primarily expect pain relief but that they also have expectations related to shoe wear and foot appearance 3,10-12,14 Schneider and Knahr 11 interviewed 200 patients who underwent surgical management for HV and found that patients considered a decrease in pain and footwear problems to be the most important factors influencing outcomes. Saro et al 10 demonstrated that correction of the HV did not affect the SF-36 outcome score, but the ability of patients to choose footwear freely was a significant factor.…”
Section: Discussionmentioning
confidence: 99%
“…More than patients with other foot and ankle pathologies, patients with HV typically expect the ability to comfortably wear shoes and increase their shoe wear variety. 1 Studies on this topic generally agree that patients primarily expect pain relief but that they also have expectations related to shoe wear and foot appearance 3,10-12,14 Schneider and Knahr 11 interviewed 200 patients who underwent surgical management for HV and found that patients considered a decrease in pain and footwear problems to be the most important factors influencing outcomes. Saro et al 10 demonstrated that correction of the HV did not affect the SF-36 outcome score, but the ability of patients to choose footwear freely was a significant factor.…”
Section: Discussionmentioning
confidence: 99%
“…21 Although these consensus statements, combined with the definition of treatment failure described above, are helpful in highlighting the indications for either a revision or salvage procedure, the optimal timing of a potential procedure will be variable based on a patient's overall health and psychological status, expectations, and perspective on additional surgery. 7 When developing treatment algorithms, clinicians should take these and the aforementioned factors into account.…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by a previous study showing that they were among the most commonly cited preoperative expectations in foot and ankle patients. 3…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a previous study showing that they were among the most commonly cited preoperative expectations in foot and ankle patients. 3 About 60% of patients had higher expectations than their surgeons to improve the abilities to exercise for fitness and run for sports or exercise. Similarly, Ghomrawi et al found that 75.6% of THA and 80.0% of TKA patients had higher expectations than surgeons for improvement in the ability to exercise or participate in sports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation